STUDENTS’ PERCEPTIONS OF USING GOOGLE TRANSLATE AS MEDIA FOR ASSISTING INDEPENDENT LEARNING IN VOCABULARY CLASS - Miftha Fitri Ramadhani; Sabarun Sabarun; Hesty Widiastuty (PROJECT (Professional Journal of English Education), 2022)
This study aimed to know how are the Students’ Perceptions of using Google Translate as media for assisting independent learning in Vocabulary class. This study was qualitative research methodology, by study case. Subject of the study in this research was the first semester students of Vocabulary class English Education Study Program of IAIN Palangka Raya. The total of the students are 57 students and the researcher took 11 students as the subjects of this research by Purposive Sampling. For the data collection; first, the researcher used the observation checklist. Second, the researcher continued with the interview instrument. The interview has 14 questions with 3 topics; students’ personality, students’ motivation and students experience. Next, researcher analyzed the data as qualitative data from interview which has been collected and using documentation to strengthen the data such as pictures screenshot of interviews in WhatsApp and Zoom Application. Based on the research problem, it can be concluded that the using of Google Translate as a media for assisting students independent learning in vocabulary class are very helpul, effective and students also feel their vocabulary increased and they motivated in the teaching learning process. And considering the conclusions drawn above, it implies that the use of Google Translate can be used to help or support independent learning and also beneficial media for students, Google Translate help them to translate English material quickly and easily. Keywords:  Perceptions, Google Translate, Vocabulary, Independent Learning, Case Study